Assessment of Azotobacter chroococcum’s Ability to Produce Hydrolytic Enzymes and Enhance Growth of Vicia faba (Baghdad Science Journal, 2019)
A. chroococcum isolate was examined for its ability to produce the hydrolytic enzymes chitinase, pectinase, protease, and lipase, in an effort to enhance the growth of fava bean (Vicia faba). Biological experiment was conducted in pots with complete random design (CRD). The experiment includes three treatments: control (plant without treatment) (P), NPK fertilizer (plant + fertilizer) (PF), and A. chroococcum inoculum (plant + A. chroococcum) (PA). These treatments were performed with sterile and non-sterile soil, which were planted with fava beans. At the end of experiment (seven weeks from planting), length and weight of plant shoot and plant root were calculated. The results show that the isolate was able to produce chitinase, pectinase, protease, and lipase enzymes. Plant growth increased with fertilizer and A. chroococcum inoculum addition. Fertilizer treatments (PF) were the best growth indicators, with the averages of shoot length and weight, and root length and weight of 19.52 cm, 15.55 gm, 19.93 cm, and 10.52 gm respectively. The averages of these indicators in A. chroococcum treatment (PA) were 16.4 cm, 8.85 gm, 17.52 cm, and 6.88 gm respectively. The percentages of increase caused by A. chroococcum inoculum addition (PA) in contrast with control treatment (P) were 12.83% and 34.4% in plant shoot length and weight respectively, and 60.98% and 38.99% in plant root length and weight. In general, growth indicators were higher in non-sterile than sterile soil, but these increases were not significant